REKONSTRUKSI STRUKTUR TARIAN POJA BERIDENTITIKAN MASYARAKAT BUGIS DI NEGERI SELANGOR: RECONSTRUCTION OF THE POJA DANCE STRUCTURE TO LINK WITH THE SELANGOR BUGIS IDENTITY - Khairul Anuar Zainudin,; Mohd Effindi Samsuddin, (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract The development and creation of the traditional Selangor Buginese “Poja” dance in 1988 is a heritage art that has undergone dance reconstruction. The reconstruction is linked to the “Pakurru Sumange” dance in South Sulawesi, Indonesia. Kaeppler’s approach to reconstruction (2007) shows that symbols in the “Poja” dance function as a representation of the Buginese community. The study is also based on the theory of creation and tradition by Hobsbawm (1983) and Shill (1981) to understand the relationship between the two aspects of dance involving the traditions of the Bugis community in Selangor. In conclusion, both processes detail the dance’s development, therefore allowing its identity to be linked to the Bugis community in Selangor. Keywords: Poja dance, Bugis community in Selangor, reconstruction, dance structure and re-creation of tradition. Abstrak Perkembangan dan penciptaan Tarian Poja masyarakat Bugis di Selangor pada tahun 1988 merupakan kegiatan seni tari yang telah melalui proses rekonstruksi semula kesenian tradisi yang berhubung kait dari tarian Pakurru Sumange di Sulawesi Selatan. Pendekatan Kaeppler (2007) tentang pembinaan semula tradisi ini, memperlihatkan simbol dalam Tarian Poja berfungsi mewakili masyarakat Bugis. Teori penciptaan dan tradisi oleh Hobsbawm (1983) dan Shill (1981) digunakan untuk memahami hubungan kedua-dua aspek tarian yang melibatkan tradisi masyarakat Bugis di Selangor. Kedua-dua proses ini memerihalkan perincian latar belakang perkembangan tarian dan menjustifikasikan hubungan identiti Tarian Poja dengan masyarakat Bugis di Selangor. Kata Kunci: Tarian Poja, masyarakat bugis negeri Selangor, rekonstruksi, struktur tari dan penciptaan semula tradisi.